Is highly protective parenting associated with child BMI? - Zubrick, Stephen R; Hancock, Kirsten J (My University, 2012)
Note: presentation differed from the published abstract. In recent decades rates of child overweight and obesity have increased, while children have become less active and more sedentary. Over the same period, parents have become increasingly concerned for children’s safety and independent mobility, even though the risks of harmful events (e.g. abductions) have not changed. Some have argued that a trend towards overprotective parenting, and subsequent restrictions on children’s independent mobility, may be linked to declines in children’s physical health, but there is limited research available supporting these claims. Using data from 2,600 families participating in Growing Up in Australia: The Longitudinal Study of Australian Children, this study aimed to establish if any relationship exists between maternal overprotection and children’s health. Longitudinal models were fitted to assess changes in physical health across the ages of 4-5 years to 8-9 years according to level of maternal overprotection, whilst controlling for a range of socio-demographic characteristics. Results showed no initial differences in overall health by maternal overprotection when children were aged 4-5 years. However as children became older, the health of children with high levels of maternal overprotection declined over time relative to children with low maternal overprotection. Logistic regression modelling also indicated that the risk of obesity for children with high maternal overprotection was twice that of children with low maternal overprotection. These results provide evidence of a link between maternal overprotection and poorer physical health outcomes for children. Further research is required to understand the mechanisms linking maternal overprotection to physical health and obesity.
Keywords: Activities -- Children's activities; Health -- Obesity; Children -- Outcomes; Childhood and child development; Health and wellbeing; Children; Health; Activities; Outcomes; Children's activities; Obesity; Childhood and child development; Health and wellbeing